2000
DOI: 10.1128/iai.68.4.1912-1918.2000
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to Tyvelose Exhibit Multiple Modes of Interference with the Epithelial Niche ofTrichinella spiralis

Abstract: Infection with the parasitic nematode Trichinella spiralis is initiated when the L1 larva invades host intestinal epithelial cells. Monoclonal antibodies specific for glycans on the larval surface and secreted glycoproteins protect the intestine against infection. Protective antibodies recognize tyvelose which caps the target glycan. In this study, we used an in vitro model of invasion to further examine the mechanism(s) by which tyvelosespecific antibodies protect epithelial cells against T. spiralis. Using c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
69
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 17 publications
0
69
0
Order By: Relevance
“…Rapid expulsion displayed by neonatal rat pups born to infected dams can be reproduced in pups born to naive dams by passive immunization with tyvelose-specific IgG (21). The protective mechanisms of the Abs have been documented in vivo (21,24) and confirmed in an in vitro model (23). Direct effects of Abs on T. spiralis larvae include entrapment of larvae in mucus as well as exclusion from and encumbrance in the epithelium (23,24).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rapid expulsion displayed by neonatal rat pups born to infected dams can be reproduced in pups born to naive dams by passive immunization with tyvelose-specific IgG (21). The protective mechanisms of the Abs have been documented in vivo (21,24) and confirmed in an in vitro model (23). Direct effects of Abs on T. spiralis larvae include entrapment of larvae in mucus as well as exclusion from and encumbrance in the epithelium (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…The protective mechanisms of the Abs have been documented in vivo (21,24) and confirmed in an in vitro model (23). Direct effects of Abs on T. spiralis larvae include entrapment of larvae in mucus as well as exclusion from and encumbrance in the epithelium (23,24). The potential for mast cells to contribute to Ab-mediated protection has not been investigated previously in neonatal rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rat monoclonal antibody (MAb) 18H (3) protects epithelial cells in vitro from infection with T. spiralis L1 larvae (28). The antibody binds to tyvelose-bearing N-glycans on L1 stage glycoproteins (15).…”
Section: Methodsmentioning
confidence: 99%
“…This mimics the location and activity of larvae in the intestinal epithelium of the animal host (36,37). Recently, we reported that L1 larvae molt and ecdyse when they are inoculated into cultures of human colonic epithelial cell line Caco-2 (28). The aims of the present study were to extend these initial findings in order to further define the requirements for ecdysis and to establish culture conditions that support development, growth, and reproduction of T. spiralis.…”
mentioning
confidence: 95%